Antibacterial and Antifungal Sesquiterpenoids from Aerial Parts of Anvillea garcinii - Perveen, Shagufta (Molecules, 2020)
Two new sesquiterpenoids belonging to the guaiane, 4α,9α,10α-trihydroxyguaia-11(13)en-12,6α-olide (1), and germacrane, 9β-hydroxyparthenolide-9-O-β-D-glucopyranoside (2), classes have been isolated from the leaves of the Saudi medicinal plant Anvillea garcinii along with seven known compounds (3–9). The structures of the new metabolites were elucidated by spectroscopic analysis, including one-dimensional (1D) and two-dimensional (2D) Nuclear Magnetic Resonance (NMR) and high-resolution electrospray ionization mass spectrometry (HR-ESIMS). The antimicrobial properties of 1–9 were screened against seven different pathogenic microbes, and compounds 1–3 showed a potent antifungal activity.